Real world efficacy and safety of the advanced hybrid closed-loop system MiniMed 780G (SmartGuard) in children under 7 years of age - López-López, Sara; Díaz-Martín, Cristina; García-de Pablo, Inés; Ovejero-Garcia, María Teresa; Garnier-Rodríguez, María Beatriz; Molina-Suárez, Ruth; Ontoria-Betancort, Cristina; Sáez-Gallego, Blanca; Domínguez-García, Ángela; Quinteiro-González, Sofía; Travieso-Suárez, Lourdes; Cabrera-Guedes, María Fátima; et al. (Frontiers in Medicine, 2025)
ObjectiveTo evaluate the safety and efficacy of the Medtronic 780G SmartGuard™ AID system in children under 7 years of age with type 1 diabetes (T1D).MethodsRetrospective analysis of data from children living with T1D under 7 years of age using the MiniMed 780G™ across three pediatric endocrinology units in the Canary Islands. Metabolic control parameters were analyzed from 14 days of pretreatment to 12 months of follow-up.ResultsThe study included 61 children under 7 years of age, 35 in Group 1 and 26 in Group 2. In Group 1, there was a significant increase in time in range (TIR) (13%, p = 0,000), along with a significant decrease in time above range (TAR) (7% for TAR1 and 3% for TAR2; p = 0,000). These improvements persisted for up to 1 year of follow-up. In Group 2, there was a significant increase in the TIR (7%; p = 0,000) and a significant decrease in the TAR (7%; p = 0,000 for TAR1 and 6.5%; p = 0,001 for TAR2). These improvements persisted for up to 6.5 months of follow-up. No significant changes were observed in the time below range (TBR) or variation coefficient (CV) in either group. No events of severe hypoglycemia or diabetic ketoacidosis occurred. Efficacy and safety were maintained in children with a TDD <8 units/day.ConclusionThe use of the Medtronic 780G™ SmartGuard™ system in children under 7 years of age with T1D is effective and safe, with benefits persisting for up to 6–12 months. The safety profile is maintained in children receiving a TDD <8 units/day.